2017
DOI: 10.1002/wsb.739
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of factors affecting bobolink population dynamics communicated with directed acyclic graphs

Abstract: North American grassland birds experienced steeper, more consistent, and widespread declines than other avian guilds in the past quarter century. Despite the surge of research into their ecology and conservation, there remains considerable uncertainty about the proximate and ultimate causes of declines and a need to clearly communicate its structural complexity among policy makers, resources managers, and stakeholders. We organized evidence from published literature about factors affecting population dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The presence of active grazing in grasslands may decrease birds’ nest success, in part because unlike adult birds, nests and chicks cannot move to avoid being trampled or depredated, and many grassland bird species appear to avoid nesting in grasslands with active grazing [ 97 ]. Because Bobolinks nest on the ground, the presence of active grazing and its impacts directly affect Bobolinks’ potential for successfully nesting and raising juvenile birds until they develop flight skills and independence [ 27 , 42 ]. In rotational grazing systems in Vermont, for example, predation and trampling by cattle accounted for a significant proportion (32%) of nest failures, significantly lowering Bobolink productivity [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of active grazing in grasslands may decrease birds’ nest success, in part because unlike adult birds, nests and chicks cannot move to avoid being trampled or depredated, and many grassland bird species appear to avoid nesting in grasslands with active grazing [ 97 ]. Because Bobolinks nest on the ground, the presence of active grazing and its impacts directly affect Bobolinks’ potential for successfully nesting and raising juvenile birds until they develop flight skills and independence [ 27 , 42 ]. In rotational grazing systems in Vermont, for example, predation and trampling by cattle accounted for a significant proportion (32%) of nest failures, significantly lowering Bobolink productivity [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colder Januarys may indirectly affect vegetation production via soil moisture, if temperatures are sufficiently low that the soil remains frozen for most of the winter, and soil water levels do not recharge until spring. Conversely, warmer temperatures and increased precipitation directly contribute to increases in arthropods [ 42 , 89 ], plants, and seeds [ 101 , 102 , 110 ] that provide a large proportion of Bobolinks’ food. Vegetation type, height, heterogeneity and density all play direct roles in availability of nest locations for birds [ 89 ], level of nest cover [ 44 ], concealment from predators ([ 110 ]; but see [ 111 ]), availability of singing perches for males [ 110 ], and in mitigating the impacts of extreme weather events or periods of resource scarcity [ 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The provincial government plan states that the current population cannot be maintained because of habitat loss on agricultural land and instead aims to maintain the population at 65% of its estimated size in 2015 (OMNRF 2015), which may be larger than the population prior to European settlement (COSEWIC 2010). Probable causes of the Bobolink population decline include habitat loss and a decrease in habitat quality on breeding grounds (COSEWIC 2010, McCracken et al 2013, OMNRF 2015, Ethier and Nudds 2017. Habitat quality on breeding grounds can be poor because of agricultural practices (e.g., hay harvest and livestock grazing) that result in direct and indirect destruction of nests (Bollinger et al 1990, Perlut et al 2006, MacDonald and Nol 2017.…”
Section: Introductionmentioning
confidence: 99%
“…For example, integrated conceptual approaches can generate novel hypotheses regarding distal anthropogenic causes of ecological phenomena simply by following the chain of causality backwards (e.g. Ethier & Nudds, 2017; Hughes et al., 2017). In our case study, climate was identified as a previously unsuspected upstream (exogenous) moderator of annual variation in farm management and Grasshopper Sparrow population growth rate fluctuations.…”
Section: Discussionmentioning
confidence: 99%